Real‐time Raman spectroscopy measurements to monitor the effect of polypropylene crosslinking on its true mechanical behaviour. (19th May 2021) - Letoffe, Adrien; Ponçot, Marc; Huchard, Thomas; Hupont, Sebastien; Hoppe, Sandrine; Royaud, Isabelle
Abstract: In‐situ Raman spectroscopy analysis to mechanical tests were performed to investigate the deformation micromechanisms of an isotactic polypropylene‐grafted maleic anhydride (PP‐g‐MAH) depending on the crosslinking degree provided by functional polyether amine molecules. The switch from brittle to highly ductile mechanical behaviours was focused in terms of microstructure modifications in real time during stretching. From the Raman spectral analysis, crystallinity index and macromolecular chains orientation factors for both crystalline and amorphous phases were determined. A new orientation factor relative to the polyether segments was proposed. The results shown allow a more complete understanding of the proper micromechanisms of deformation involved in each phase and their interaction between one another. These results also highlight the impact of the crosslinking reaction on the material resilience improvement. Abstract : Different polypropylene‐grafted maleic anhydrides were crosslinked by polyether amine molecules, and their mechanical behaviours were characterised by in‐situ Raman spectroscopy analysis to mechanical tests. The Raman spectra were analysed to enlighten the involved deformation micromechanisms and the microstructural modifications. A new orientation factor proper to the polyether segments inside the polymer matrix was then proposed. Raman results highlight the impact of the crosslinking reaction on the switch of mechanical behaviours from brittle to ductile.